Microstructure and crystal imperfections of nanosized CdSxSe1−x thermally evaporated thin films - Akl, Alaa A.; Hassanien, A.S. (Superlattices and microstructures, 2015)
•Thermally evaporated nanosized CdSxSe1−x thin films (0⩽x⩽0.4) have been synthesized.•XRD results indicate than CdSxSe1−x thin films have semicrystalline phase.•Dependence of microstructural and crystal imperfection upon Se content were studied.•Comparative study of quantitative elemental analysis of CdSSe system has been achieved.•Present films are useful for optoelectronic devices and photovoltaic applications. Cadmium sulfoselenide CdSxSe1−x thin films were thermally evaporated onto preheated glass substrates (523K). The evaporation rate and film thickness were kept constant at ≈2.5nm/s and 375±5nm, respectively. Microstructure and crystal imperfections of deposit CdSxSe1−x thin films were studied using X-ray diffraction (XRD) and energy dispersive analysis by X-ray (EDAX). XRD analysis reveals the formation of films have the semi-crystalline nature and the hexagonal structure with preferential 〈002〉 direction. The microstructural parameters such as, lattice parameters, the crystallite size (D), microstrain 〈ε〉, residual internal stress (S), dislocation density (δ) and number of crystallite per unit volume (N) were calculated and found to be dependent upon the composition. The presence percentage of Cd, S and Se elements in the chalcogenide CdSxSe1−x thin films were estimated by EDAX and a comparative study with other similar samples of the previous literature was discussed.